Relevasi Tersembunyi: Menguak Esensi Rahasia Angka "666" dalam Wahyu 13:16-18 - Tampilang, Risno; Maramis, Trivena (THEOLOGIA INSANI: Jurnal Theologia, Pendidikan, dan Misiologia Integratif, 2025)
This article aims to uncover the mystery or relevance of the number "666" in Revelation 13:16-18 with an apocalyptic approach and provide a contextual understanding of the church today. The method used is qualitative with a literature study type and an apocalyptic approach in understanding the text of Revelation 13:16-18. The results of the study indicate that the mystery or revelation of the number '666' refers to the authoritarian and oppressive government system that occurred in the latter half of the first century AD under the reign of Emperor Domitian. The number '666' specifically refers to Domitian as a representation of human power that opposes divine authority. In conclusion, the sign '666' is not a futuristic prediction of modern technology or a sign of the end times, but rather a symbol of Emperor Domitian's authoritarian government system in the oppression of Christians at that time. The implication for the church today is the need to be vigilant against systems of power that oppress religious freedom, while maintaining Christian faith and values ​​amidst world pressure.